Ambivalence over Emotional Expression and Perceived Social Constraints as Moderators of Relaxation Training and Emotional Awareness and Expression Training for Irritable Bowel Syndrome - Holmes, Hannah J. (Gen Hosp Psychiatry, 2018)
OBJECTIVE: Psychological treatments are generally beneficial for patients with irritable bowel syndrome (IBS), but patients’ responses vary. A prior randomized controlled trial found that both relaxation training (RT) and emotional awareness and expression training (EAET) were superior to a waitlist control condition for IBS symptoms, quality of life, depression, and anxiety among IBS patients [1]. METHOD: We conducted secondary analyses on these data to examine potential moderators of treatment outcomes. Baseline measures of patients’ ambivalence over emotional expression and perceived social constraints, which have been hypothesized to influence some treatments, were tested as possible moderators of the effects of RT and EAET, compared to the control condition. RESULTS: Results indicated that these variables moderated the effects of RT but not EAET. The benefits of RT occurred for patients who reported higher ambivalence over emotional expression or perceived social constraints, whereas the benefits of EAET were not influenced by these factors. CONCLUSION: These findings suggest that RT might be particularly helpful for people who tend to avoid emotional disclosure and expression, supporting the possible benefit of targeting treatments to patient characteristics and preferences, whereas EAET might be helpful for a broader range of patients with IBS.